1997
DOI: 10.1038/37641
|View full text |Cite
|
Sign up to set email alerts
|

Miranda directs Prospero to a daughter cell during Drosophila asymmetric divisions

Abstract: Asymmetric cell division is a general process used in many developmental contexts to create two differently fated cells from a single progenitor cell. Intrinsic mechanisms like the asymmetric transmission of cell-fate determinants during cell division, and extrinsic cell-interaction mechanisms, can mediate asymmetric divisions. During embryonic development of the Drosophila central nervous system, neural stem cells called neuroblasts divide asymmetrically to produce another multipotent neuroblast and a ganglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
217
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 300 publications
(222 citation statements)
references
References 24 publications
3
217
0
Order By: Relevance
“…Our results showed that, in the larval brain, Loco is colocalized with Miranda and Rap/Fzr in the basal axis, whereas during asymmetric division of embryonic neuroblasts, Loco is expressed in the apical axis (Yu et al 2005). Although Miranda is a known mediator of asymmetric division of embryonic neuroblasts and a specific marker for larval neuroblasts, its function in postembryonic development has not been completely elucidated (Ikeshima-Kataoka et al 1997;Shen et al 1998;Slack et al 2006). Colocalization of Loco with Miranda and Rap/Fzr (Figure 7) suggests a possible functional role for these molecules during postembryonic neuroblast division.…”
Section: Discussionmentioning
confidence: 65%
“…Our results showed that, in the larval brain, Loco is colocalized with Miranda and Rap/Fzr in the basal axis, whereas during asymmetric division of embryonic neuroblasts, Loco is expressed in the apical axis (Yu et al 2005). Although Miranda is a known mediator of asymmetric division of embryonic neuroblasts and a specific marker for larval neuroblasts, its function in postembryonic development has not been completely elucidated (Ikeshima-Kataoka et al 1997;Shen et al 1998;Slack et al 2006). Colocalization of Loco with Miranda and Rap/Fzr (Figure 7) suggests a possible functional role for these molecules during postembryonic neuroblast division.…”
Section: Discussionmentioning
confidence: 65%
“…Asymmetric segregation of Pros protein and pros RNA is mediated by the adaptor protein Miranda (Mira). Once segregated to the GMC, Mira is degraded, thereby releasing Pros from the cortex (Ikeshima-Kataoka et al 1997;Shen et al 1997;Matsuzaki et al 1998). Pros can then enter the nucleus, where it has been thought to specify GMC identity by promoting the expression of GMC-specific genes and repressing the expression of neuroblast-specific genes (but see Choksi et al 2006).…”
Section: Neurogenesis In Drosophila (A) Neuroblast Formation: Notch Smentioning
confidence: 99%
“…the coiled-coil Miranda (Mira) protein, the transcription factor Prospero (Pros), the RNA-binding protein Staufen, and its cargo pros mRNA form one complex (Hirata et al, 1995;Ikeshima-Kataoka et al, 1997;Knoblich et al, 1995;Shen et al, 1997;Spana and Doe, 1995) and Partner of numb (Pon) and Numb form another complex (Lu et al, 1998;Rhyu et al, 1994). Formation of the apical cortical domain is necessary for proper basal targeting; loss of Par3-Par6-aPKC components results in a uniform cortical distribution of Pros and Mira at metaphase (Petronczki and Knoblich, 2001;Schober et al, 1999;Rolls et al, 2003;Wodarz et al, 1999).…”
mentioning
confidence: 99%